A STUDY OF ESSENTIAL BASIC VALUES WHICH SUPPORT SOCIAL HARMONY IN CONFLICT-PRONE AREAS - Aunurrahman Aunurrahman (JETL (Journal of Education, Teaching and Learning), 2016)
Basically this study intended to find out essential basic values which support social harmony in conflict-prone areas, with a profound study at primary schools in Sambas regency, west Kalimantan. As revealed by a number of data sources, west Kalimantan is one of the areas which is prone to conflict. This is evidenced by the happening of several ethnic conflicts including in Sambas regency so that it is an important policy of the regional government to find a solution in order to prevent similar conflicts from happening again in the future.The profound study at primary schools is deemed highly essential since social harmony values should be instilled among the students at an early age. In addition to that, teachers are knowledgeable about the foundation which creates an attitute of harmony among their students.The method used in this research is a qualitative one, with primary school teachers as the subject of the research. They represent three characteristic areas, namely: the urban area, the suburban area and the remote area of Sambas regency. Primary data collection was carried out through interview and focus group discussion (FGD), with the interactive model proposed by Miles & Huberman as technique of qualitative data analysis. The findings obtained from data collection and analysis revealed that social harmony has an important and profound meaning for society in Sambas regency. Basically there are three pillars of essential basic values which serve as the framework of social harmony, namely: (a) the basic values of mutual respect, (b) the basic values of tolerance and togetherness, and (c) the basic values of freedom and responsibility. Internalization of these basic values happen intensively especially in families through custom formation at households and society in Sambas regency. Meanwhile at schools these basic values are developed and reinforced through more formal custom formation by the teachers and school regulations.